2003
DOI: 10.1042/bst0310652
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Toll-like receptor 4 and the systemic inflammatory response syndrome

Abstract: The systemic inflammatory response syndrome (SIRS) is a major cause of morbidity and mortality, and is thought to be due to an over-amplification of an inflammatory response. The Toll-like receptor 4 ( TLR4 ) Asp-299-->Gly polymorphism has been shown to reduce lipopolysaccharide responsiveness. We examined whether this TLR4 polymorphism is associated with severity of SIRS. A trend was found between the minor allele and mortality in SIRS (odds ratio of 4.3; P =0.076), suggesting a role for TLR4 signalling in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
6

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 7 publications
2
46
1
6
Order By: Relevance
“…[13][14][15] Studies that have not demonstrated an association were focused primarily on endotoxin responses in circulating leukocytes, 20,22,24,25 which mimics endotoxemia and clinical sepsis. 19,21 Numerous factors, including LBP, CD14 and serum HDL, among other molecules modulate LPS recognition and binding to TLR4, and interindividual differences in their effects may have important influences on leukocyte responses to endotoxin measured in our studies and seen clinically.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[13][14][15] Studies that have not demonstrated an association were focused primarily on endotoxin responses in circulating leukocytes, 20,22,24,25 which mimics endotoxemia and clinical sepsis. 19,21 Numerous factors, including LBP, CD14 and serum HDL, among other molecules modulate LPS recognition and binding to TLR4, and interindividual differences in their effects may have important influences on leukocyte responses to endotoxin measured in our studies and seen clinically.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, other clinical and basic science investigations have failed to demonstrate a role for TLR4 in altering the inflammatory response. [19][20][21][22][23][24][25] There are several possibilities that may explain the lack of association between TLR4 genotype and measures of endotoxin signaling we have observed. [26][27][28] First, as there were no individuals homozygous for the TLR4 þ 896G allele, the remaining wild-type TLR4 allele in heterozygous carriers may be sufficient to elicit a normal response to endotoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an association of this TLR4 SNP with an increased risk of Gram negative infections and septic shock has been demonstrated (Agnese et al, 2002;Lorenz et al, 2002;Schrö der and Schumann, 2005). However, contrasting data have been obtained in other studies (Child et al, 2003;Erridge et al, 2003;Read et al, 2001;Heesen et al, 2003;Imahara et al, 2005;Schippers et al, 2005;von Aulock et al, 2003;Yang et al, 2004). Changes in eicosanoid levels are also correlated with SNPs in the promoter region of PTGS2 and 5-Lo genes, respectively codifying the cyclooxygenase-(Cox)-2 and 5-lipoxygenase (5-Lo), enzymes involved in arachidonic acid metabolism.…”
Section: Introductionmentioning
confidence: 93%
“…The initially identified and best studied D299G polymorphism (an amino acid substitution, from aspartic acid to glycine at position 299 in the TLR-4 gene) is associated with an increased frequency of Gram-negative infection and increased severity of Gram-negative sepsis (Child et al, 2003). also been linked to a rare, heterozygous missense TLR4 mutation (Smirnova et al, 2003).…”
Section: Tlrs and Human Disease Processesmentioning
confidence: 99%